Analisis Strategi Pengembangan Sapi Pakan Alternatif dari Pelepah Kelapa Sawit di Kabupaten Asahan - Ajiputra, Rohardian; Hasnudi, Hasnudi; Pane, Erwin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
This research was conducted in Asahan Regency, to see the study in general. Meanwhile, a detailed study was conducted in the sub-districts chosen to represent all the sub-districts in Asahan Regency. The study was conducted for 2 (two) months, from September to December 2016. The research sample was 70 cattle farmers spread in Air Batu District as many as 37 people, Aek Kuasan District as many as 25 people and Meranti District as many as 8 people. Analysis of the development strategy was carried out using the SWOT (Strengths Opportunities Weaknesses and Threat) analysis method. The conclusion is that the development of cattle business which is given alternative feed for oil palm fronds in Asahan Regency is still possible because the strength and pelauang factors have the greatest value from the weakness and threat factors. The priority sequence of strategies for developing cattle business which is given alternative feed for oil palm fronds in Asahan Regency is to form cattle breed cooperatives so that there is no price difference that is too large, improve the quality of human resources for cattle farmers, develop product innovations, increase access to capital to increase production , increasing cooperation with oil palm farmers in order to obtain raw material for midribs, increasing demand for cattle by expanding markets, developing efficient marketing systems, improving the quality of cattle.